2014
DOI: 10.3844/ajebasp.2014.122.132
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Service-Learning Curriculum at a Local at-Risk High School: An Examination of Preliminary Data

Abstract: Over the years, there has been substantial research highlighting the effectiveness of service-learning from the perspective of the student in the classroom. Multiple studies have demonstrated student-learning outcomes as well as provided descriptions of service-learning projects and syllabi. However, limited research has been conducted exploring the effects of service-learning on the community. This pioneering study offers preliminary data on the contribution of service-learning to the community by exploring t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…In previous studies, we have reported on similar service-learning interventions with diverse populations from regular public schools (Helm-Stevens, Dickerson, & Fall, 2019;Helm-Stevens et al, 2014). The comparison of those studies to this data shows a much greater impact reported by the juvenile offenders, both in the magnitude and pervasiveness of the effects.…”
Section: Discussionsupporting
confidence: 53%
“…In previous studies, we have reported on similar service-learning interventions with diverse populations from regular public schools (Helm-Stevens, Dickerson, & Fall, 2019;Helm-Stevens et al, 2014). The comparison of those studies to this data shows a much greater impact reported by the juvenile offenders, both in the magnitude and pervasiveness of the effects.…”
Section: Discussionsupporting
confidence: 53%
“…The few studies that have examined community benefits attempt to offer insight by utilizing data obtained from community organizations, not the community itself (Vernon & Ward, 1999;Ferrari & Worrall, 2000;Bushouse, 2005;Miron & Moely, 2006;Sandy & Holland, 2006;Worrall, 2007;Helm-Stevens, Fall, Havens, Garcia & Polvi, 2014). Due to these various challenges, the available research often results in equivocal qualitative findings, thus necessitating a literary expansion in quantitative research on the community impact of service-learning.…”
Section: Prior Researchmentioning
confidence: 99%